Influence the Management, Use and Occupation of Land in the Mobility and Contamination by Phosphorus in Watersheds of Pantanal Matogrossense-Brazil: Contribution to Public Policy in the Region - Silva, Dirce Arruda da; Fraceto, Leonardo Fernandes [UNESP]; Rosa, Andre Henrique [UNESP]; Lee, G. (Information Engineering Research Inst, Usa, 2013)
The contribution of phosphorus (P) from agricultural and urban areas surrounding the Pantanal-Brazil, one of the most biodiverse environments on the planet, designated by UNESCO as a World Natural Heritage Site, may in the long term, cause irreparable damage to that environment. Thus, this study aims to determine the forms of P in surface waters of the Cuiaba subacia bays and region, in order to understand and quantify the level of contamination by P due to agricultural activities and urban. The results obtained in this work will able the provision of subsidies for public policies related to the management and conservation of the Pantanal-Brazil, from diagnosis influence the use and occupation of land in water quality from rivers and lakes in the region.
Keywords: Management; Public Policy; Environmental